An overview and prediction of 100 mm performance over 40 years during the Athletics World Championships - Kotula, K.; Loturco, I.; Matusinski, A.; Zajac, A.; Maszczyk, A. (Biology of Sport, 2025)
The primary aim of this study was to determine whether the significant improvements in 100 m-meter sprint times over the past 40 years are the result of an overall enhancement in performance among all elite sprinters, or are mainly driven by the sporadic emergence of exceptionally talented individuals. Additionally, we compared the average age of the semifinalists with that of the champion. To explore this broader research question, we compared the average performance times and ages of World Championship semifinalists with those of the champions over successive 2-year intervals. This approach allowed us to ascertain whether there has been a consistent improvement in average performances among elite sprinters or whether progress is mainly due to extraordinary athletes who occasionally set new records. By analyzing these patterns, we aimed to understand the underlying factors contributing to advancements in sprint performance and to assess whether these improvements are widespread or concentrated among a few exceptional individuals. Finally, we analyzed the relationship between age and 100 m-meter performance and predicted the results of semifinalists and winners at the Athletics World Championships in 2025 and 2027, for both men and women. The results obtained suggest that progress in sprinting, in both sexes, depends on the emergence of exceptionally talented individuals who set new world records or achieve world-leading times during the main competitions of the season. These exceptionally talented athletes have improved the winning times in the main 100 m-meter competitions, while the average times of semifinalists at the Athletics World Championships have remained relatively constant, ranging between 10.40 and 10.50 seconds over the analyzed 40-year period.